ANALISIS METODE PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 TERHADAP PERKEMBANGAN KOGNITIF ANAK BERDASAR TEORI PERKEMBANGAN KOGNITIF ANAK PIAGET - Intan Nur Amelia (Lembaga P3M, 2022)
This study aims to examine the analysis of e-learning methods during the COVID-19 pandemic on children's cognitive development based on Piaget's theory of cognitive development. Education for children is a systematic effort to deliver children to a bright future. In essence, every child is the future successor of the civilization of the Indonesian nation with its role as a supply of human resources. Whereas on the other hand, efforts to fulfill children's rights to receive education when related to current conditions have turned out to be experiencing obstacles due to the Covid-19 pandemic that has hit all parts of the world, including Indonesia. Official data released by the Government of Indonesia as of August 15, 2021, as many as 213 countries have been infected with Covid-19, of which 139,226,143 have been confirmed positive and 2,989,984 have died,. If we take some of the characteristics of children at the stage of Piaget's cognitive development associated with online school policies, then there are things that need to be anticipated, namely the cognitive phase of children directly requiring school education, even though literally schools are interpreted only as institutions or buildings used for learning activities. and teach according to the level of education (elementary school, middle school and high school), but actually the school is not only an institution that provides subject matter and physical buildings but also as a laboratory for children's mindset and mentality. This study uses the library method where in collecting data information with documentation techniques, namely seeking data on relevant matters from various sources such as documents, books, scientific journals and news. The result of this research is that online learning on children's cognitive development directly experiences obstacles. This is evidenced from the concepts and theories of Piaget's cognitive development where the hallmark of cognitive development is the existence of strong interpersonal and social relationships with the environment. Because basically the learning process is not only limited to the process of delivering information and knowledge, but also there must be reciprocal interaction between participants and teachers so that there is a change in behavior and knowledge in a concrete direction. Keyword: covid-19, Education, e-learning methods, Piaget, school